2017
DOI: 10.1016/j.beproc.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary antioxidants and exercise training on the escape performance of Southern Corroboree frogs

Abstract: Escape-response behaviour is essential to ensure an individual's survival during a predator attack, however, these behaviours are energetically costly and may cause oxidative stress. Oxidative stress can be reduced by supplementing an individual's diet with exogenous antioxidants or through regular moderate exercise training, which stimulates the upregulation of the endogenous antioxidant system. Two studies have tested the simultaneous effects of dietary antioxidant supplementation and exercise training on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Our findings provide no evidence that dietary b-carotene improves exercise performance and promotes exploration behavior in P. corroboree. This was unexpected because our past dietary studies with P. corroboree have demonstrated that a mixed carotenoid dietary supplement (administered at a comparable dose to the present study, 1-1.5 mg/g) improved P. corroboree escape response performance and exercise endurance during both aquatic and terrestrial escape response trials (Silla et al, 2016;McInerney et al, 2017). The discrepancy in findings between our lab studies and present field study may have arisen because complex environmental conditions at the release site elicited more variable behavioral responses, regardless of an individual's diet and physiological state.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Our findings provide no evidence that dietary b-carotene improves exercise performance and promotes exploration behavior in P. corroboree. This was unexpected because our past dietary studies with P. corroboree have demonstrated that a mixed carotenoid dietary supplement (administered at a comparable dose to the present study, 1-1.5 mg/g) improved P. corroboree escape response performance and exercise endurance during both aquatic and terrestrial escape response trials (Silla et al, 2016;McInerney et al, 2017). The discrepancy in findings between our lab studies and present field study may have arisen because complex environmental conditions at the release site elicited more variable behavioral responses, regardless of an individual's diet and physiological state.…”
Section: Discussionmentioning
confidence: 50%
“…In the absence of any beneficial effects of b-carotene on exploration behavior at higher doses, research attention should turn towards testing the effects of mixed carotenoid supplements on exploration behavior at the time of release. We make this recommendation given that dietary supplements containing carotenoid mixes have been found to improve P. corroboree physiological performance under controlled lab conditions (Silla et al, 2016;McInerney et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…P. corroboree enter hibernation during the onset of austral winter and evade freezing by burrowing into underground refuges (at the base of tussock grasses, under logs, and in sphagnum bogs) (Osborne, 1991;McFadden, 2019, personal comms). Past studies with P. corroboree have shown that dietary carotenoids can improve escape-response performance (Silla et al, 2016;McInerney et al, 2017), and modify exploratory behaviour (Kelleher, et al, 2019). In the present study, we tested the effect of carotenoid supplementation on the post-hibernation performance of adult P. corroboree following initial arousal from hibernation (24-48 hrs post-arousal) and following recovery from hibernation (six weeks post-arousal) to explore whether exogenous antioxidants play a role in post-hibernation performance.…”
Section: Introductionmentioning
confidence: 97%
“…The aim of this study was to investigate the influence of two dietary carotenoids (β-carotene and lutein), each supplemented at two doses (0.1 mg g −1 and 1 mg g −1 ), on the growth and development of the critically endangered southern corroboree frog, Pseudophryne corroboree . Dietary carotenoids have previously been found to affect P. corroboree escape-response, skin colouration, and cutaneous bacterial communities (Silla et al , 2016; Umbers et al , 2016; Edwards et al , 2017; McInerney et al , 2017). Based on this knowledge, P. corroboree is expected to require dietary carotenoids for multiple physiological processes.…”
Section: Introductionmentioning
confidence: 99%